2002
DOI: 10.4269/ajtmh.2002.66.299
|View full text |Cite
|
Sign up to set email alerts
|

Low cellular response in vitro among subjects with long-term exposure to malaria transmission in Brazilian endemic areas.

Abstract: Abstract. The cellular and humoral immune responses to Plasmodium falciparum and P. vivax recombinant circumsporozoite (rCS) proteins were studied in two populations in the Brazilian malaria-endemic region. One group of subjects lived in an urban area that was free from the risk of malaria and was exposed to the disease through short visits to the endemic area. The other group had lived for approximately 10 years in a rural area, where they were continuously exposed to transmission. Proliferative responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
15
0
3
Order By: Relevance
“…46 It is worth noting that in a recent Brazilian study proliferative responses to recombinant CSP were observed in 50% of the adults not continuously exposed to malaria, but in only 10% of subjects from a transmission area. 47 As in our study, antibody responses were similar in both groups. These studies are very complementary and point to the likely effect of recent infection on immunomodulation/lymphocyte trafficking, and also highlighted the importance of timing of blood collection when analyzing T cell responses.…”
Section: H-2 Haplotype (H-2 D )supporting
confidence: 71%
“…46 It is worth noting that in a recent Brazilian study proliferative responses to recombinant CSP were observed in 50% of the adults not continuously exposed to malaria, but in only 10% of subjects from a transmission area. 47 As in our study, antibody responses were similar in both groups. These studies are very complementary and point to the likely effect of recent infection on immunomodulation/lymphocyte trafficking, and also highlighted the importance of timing of blood collection when analyzing T cell responses.…”
Section: H-2 Haplotype (H-2 D )supporting
confidence: 71%
“…While an early proinflammatory response is required to reduce the parasite load, immunoregulatory mechanisms can prevent further organ damage once parasitemia is under control and may cause the suppression of T-cell responses to both malarial and unrelated antigens, which is often observed in malaria-exposed populations (2,17,18).…”
mentioning
confidence: 99%
“…This suggested that natural exposure to Plasmodium infection primes CD8 ϩ T cells specific for liver stages that were recalled by the recombinant vaccine [30]. Therefore, it was apparent that CD8 ϩ T cells against liver-stage antigens, albeit at low frequencies, are present in these vaccinees before vaccination and generally in individuals in malaria-endemic areas [31][32][33][34][35], where the development of immunity to liver stages is irrevocably associated with concomitant blood-stage parasitemia.…”
Section: Discussionmentioning
confidence: 99%